Use of the GlideScope Ranger Video Laryngoscope for Emergency Intubation in the Prehospital Setting: A Randomized Control Trial*. Issue 7 (July 2016) - Trimmel, Helmut; Kreutziger, Janett; Fitzka, Robert; Szüts, Stephan; Derdak, Christoph; Koch, Elisabeth; Erwied, Boris; Voelckel, Wolfgang G.
Abstract : Objectives: We sought to assess whether the GlideScope Ranger video laryngoscope may be a reliable alternative to direct laryngoscopy in the prehospital setting. Design: Multicenter, prospective, randomized, control trial with patient recruitment over 18 months. Setting: Four study centers operating physician-staffed rescue helicopters or ground units in Austria and Norway. Patients: Adult emergency patients requiring endotracheal intubation. Interventions: Airway management strictly following a prehospital algorithm. First and second intubation attempt employing GlideScope or direct laryngoscopy as randomized; third attempt crossover. After three failed intubation attempts, immediate use of an extraglottic airway device. Measurements and Main Results: A total of 326 patients were enrolled. Success rate with the GlideScope ( n = 168) versus direct laryngoscopy ( n = 158) group was 61.9% (104/168) versus 96.2% (152/158), respectively ( p < 0.001). The main reasons for failed GlideScope intubation were failure to advance the tube into the larynx or trachea (26/168 vs 0/158; p < 0.001) and/or impaired sight due to blood or fluids (21/168 vs 3/158; p < 0.001). When GlideScope intubation failed, direct laryngoscopy was successful in 61 of 64 patients (95.3%), whereas GlideScope enabled intubation in four of six cases (66.7%) where direct laryngoscopy failed ( p = 0.055). In addition, GlideScope was prone to impaired visualization of the monitor because of ambient light (29/168; 17.3%). There was no correlation between success rates and body mass index, age, indication for airway management, or experience of the physicians, respectively. Conclusions: Video laryngoscopy is an established tool in difficult airway management, but our results shed light on the specific problems in the emergency medical service setting. Prehospital use of the GlideScope was associated with some major problems, thus resulting in a lower intubation success rate when compared with direct laryngoscopy.